Participation and quality of life of Nepalese children with visual impairment in comparison with normally sighted peers: a cross sectional comparative study - Srijana Adhikari; Ellen Bernadette Maria Elsman; Ruth Marie Antoinette van Nispen; Fleur Van Rens; Manish Poudel; Gerardus Hermanus Maria Bartholomeus van Rens (Journal of Patient-Reported Outcomes)
Abstract Background Poor vision compromises quality of life and participation in different daily life activities of children such as, sports, leisure time, interactive play and social interaction. The purpose of this cross - sectional study is to investigate participation and quality of life of children with visual impairment (VI) and blindness compared with normally sighted peers. Methodology Children aged 7–17 years with blindness (n = 100), moderate to severe VI (n = 100) and normal sight (n = 100) completed Nepalese versions of the Participation and activity inventory children and youth (PAI-CY 7–12 and 13–17), L. V. Prasad functional vision questionnaires (LVP-FVQ II) and Pediatric Eye Questionnaires (PedEyeQ 5–11 and 12–17). The measurement properties of PAI -CY was studied. All (sub) scores were compared between three groups. Associations between the severity of VI and outcomes were assessed with age and sex adjusted linear regression analyses. Results Children with blindness scored worse than children with VI, who scored worse than normally sighted children on the PAI-CY 7–12, the physical functioning subscale of the PAI-CY 13–17 and the LVP-FVQ II(p = < 0.001).However, for the psychosocial functioning subscale of PAI-CY 13–17, children with blindness scored better than children with VI(p = < 0.01). On the PedEyeQ, young children (5–11) with blindness on all subscales, and older children (12–17 years) with blindness on the functional vision subscale scored worse than children with VI(p = < 0.01).Regression models showed that both moderate/severe VI and blindness were significantly associated with worse PAI-CY, LVP-FVQ II, PedEyeQ 5–11 and PedEyeQ 12–17 functional vision subscale scores(p = < 0.01). Conclusion Younger children with blindness showed worse participation and quality of life compared to children with VI, whereas results for older children showed a mixed pattern with children with blindness showing better participation in psychosocial domain. Appropriate low vision rehabilitation interventions are needed for children with VI and blindness to increase their participation and quality of life to the level of their normally sighted peers as far as possible. Future studies could include children who do not attend school and may have worse participation and quality of life than children in our study.